Bridging the Gap: Integrating Food Security into Healthcare for Healthier Futures – A Scoping Review - Nor Faiza Mohd Tohit; Roselawati Mat Ya; Mainul Haque (Advances in Human Biology)
Food insecurity remains a critical public health challenge, significantly affecting health outcomes and contributing to the burden of chronic diseases. Integrating food security initiatives within the healthcare systems offers a strategic approach to addressing this issue by leveraging healthcare infrastructure to identify, support and manage the nutritional needs of vulnerable populations. This article explores the multifaceted role of policy development, stakeholder engagement and technological innovation in fostering effective integration of food security into the healthcare systems. The study highlights the importance of comprehensive training and capacity building for healthcare professionals to effectively recognize and respond to food insecurity. By embedding food security into medical curricula and professional development programmes, healthcare providers can improve patient care and health outcomes. Despite the promising benefits, several challenges impede progress, including limited research on integrated food security interventions’ long-term impacts and economic benefits. Programs’ cultural relevance and adaptability also require further exploration to ensure effectiveness across the diverse populations. The paper underscores the need for robust metrics and continuous improvement methodologies to evaluate the impact of these initiatives, facilitating the replication of successful models in varied settings. Furthermore, the paper identifies critical research gaps and proposes future research directions to enhance the understanding and effectiveness of food security integration. These include longitudinal impact studies, economic evaluations, and exploration of interdisciplinary collaborations. In conclusion, while challenges remain, integrating food security initiatives within healthcare systems presents a significant opportunity to improve public health outcomes and reduce food insecurity. With collaborative efforts from policymakers, healthcare providers and communities, these initiatives can pave the way towards a future where food security is integral to health and well-being, ultimately contributing to healthier and more resilient communities.